An eventful journey from menarche to successful motherhood - Salil B Chakrabarti; Maureen P Tigga; Jayanta Ray; Amulya Debbarma (Wolters Kluwer Medknow Publications, 2016)
Herlyn-Werner-Wunderlich syndrome is an uncommon variant of mullerian duct anomaly and the approach to its diagnosis requires a high index of suspicion and vigilant work up. Presented here is a case of a 26yearold woman who had the aforementioned anomaly and was pursued for nearly 10 years to provide her with a fruitful obstetric outcome after having undergone Strassman's metroplasty at a young age of 15 years.